2001
DOI: 10.1002/cm.1027
|View full text |Cite
|
Sign up to set email alerts
|

Vascular smooth muscle cell phenotypic modulation in culture is associated with reorganisation of contractile and cytoskeletal proteins

Abstract: Smooth muscle cells (SMC) exhibit a functional plasticity, modulating from the mature phenotype in which the primary function is contraction, to a less differentiated state with increased capacities for motility, protein synthesis, and proliferation. The present study determined, using Western analysis, double-label immunofluorescence and confocal microscopy, whether changes in phenotypic expression of rabbit aortic SMC in culture could be correlated with alterations in expression and distribution of structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
141
0
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(156 citation statements)
references
References 58 publications
7
141
0
8
Order By: Relevance
“…Indeed, reduced level of CNN1 protein was observed in tumor cells and proliferating SMCs, whereas upregulation of CNN1 suppressed SMC proliferation. 18,59,60 Our study also confirmed the negative relationship between CNN1 protein level and SMC proliferation. The slowly proliferating XBP1-deficient cells possessed higher level of CNN1, and overexpression of CNN1 via Ad-CNN1 gene transfer reduced SMC proliferation.…”
Section: Arterioscler Thromb Vasc Biolsupporting
confidence: 81%
“…Indeed, reduced level of CNN1 protein was observed in tumor cells and proliferating SMCs, whereas upregulation of CNN1 suppressed SMC proliferation. 18,59,60 Our study also confirmed the negative relationship between CNN1 protein level and SMC proliferation. The slowly proliferating XBP1-deficient cells possessed higher level of CNN1, and overexpression of CNN1 via Ad-CNN1 gene transfer reduced SMC proliferation.…”
Section: Arterioscler Thromb Vasc Biolsupporting
confidence: 81%
“…Mature SMCs can undergo reversible changes of phenotype (phenotype modulation or switching) in response to changes in the local environment (15,24). Previous studies of smooth muscle differentiation and phenotype modulation indicate that SMC express the contractile differentiated phenotype when the cells are not in a proliferated state (15).…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] Cytoskeletal dynamics 29 and organization play a crucial role in maintaining SMC differentiation. 30,31 Impaired Rho signaling in PKC␦ deficient SMCs was associated with a disassembly of stress fibers ( Figure 8A).…”
Section: Loss Of Pkc␦ Causes Smc Dedifferentiationmentioning
confidence: 99%